Mini Nurse Lite, Medical Tool Quiz and More: Smartphone Apps as Interactive English Medical Materials for Nursing Students - Handayani, Fitri (Elsya : Journal of English Language Studies, 2021)
Gaining medical knowledge in English is challenging for nursing students due to the various challenging necessities such as possessing specialized vocabulary, diagnosing symptoms clearly, and writing health reports. To overcome these classical and practical language barriers, this study tries to establish the effects of using selected smartphone apps, i.e., Mini Nurse Lite, Disease Dictionary, Surgical & Medical Instruments, and Medical Tool Quiz, to increase nursing students’ ability in understanding English medical materials. This research employed a quasi-experimental pre-test and post-test design. The participants were 76 first-year nursing students of a selected university in Solok. The experimental treatment was teaching English medical materials through smartphone applications followed by discussion class, while the control group did not receive training in nursing with smartphone applications as only lecture-based education was performed. The results of the study showed that there was a higher mean score in levels of satisfaction by students in the experimental group (88.53) compared to the control group (82.27). It indicates that smartphone applications were effective for improving nursing students’ ability in understanding English medical materials. The findings suggest optimal conditions for designing smartphone-based learning to be applied in a nursing class and contributed to the lack of studies on smartphone-based instruction in nursing within the context of overcoming English language barriers.